Development of New Sensitive Spectrophotometric Method for Estimation of Famciclovir Using 3-Amino Phenol - Babu, N. Raghavendra; Divya, A.; Padmavathi, Y.; Vinoda, T.; Sree, M. Subha; lakshmi, A.G.Prasanna (Asian Journal of Pharmaceutical Research and Development, 2023)
The study aims to find out the effectiveness of the combination of citral and curcumin as antifungal compounds. Lemongrass (Cymbopogon citratus) is a valuable family of grass known due to its flavoring, medicinal, and fragrance application. Haldi (Turmeric) scientifically known as Curcuma longa belongs to familthey Zingiberaceae. Its polyphenolic compound curcumin has been showing a variety of antifungal investigations due to extensive traditional uses and very low side effects.Turmeric has beenutilized in traditional medicine for various diseases counting diabetes, hepatitis, hemorrhoids, hysteria, indigestion, skin disease, inflammation, anorexia, hepatic disorders, cough, and sinusitis. In this formulation substudy combination of two bioactive oils is considered to form an effective antifungal spray preparation. The spray preparation is helpful to achieve fast absorption of the drugs through the transdermal way of drug administration. The effectiveness and activity rate of spray preparation is more beneficial. Lemongrass oil and curcumin are dissolved in ethanol to form a stable, safe, and effective spray formulation.